2003
DOI: 10.1021/jp026227t
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Property Relationships in Phosphole-Containing π-Conjugated Systems:  A Quantum Chemical Study

Abstract: The aim of this theoretical study is to provide an in-depth interpretation of the UV-vis absorption spectra and electrochemical data of two series of 2,5-dipyridyl-and 2,5-dithienylphosphole derivatives containing σ 3 -or σ 4 -P atoms. The geometric and electronic structures of those phosphole-containing π-conjugated systems were investigated using density functional theory (DFT). To assign the absorption peaks observed in the UV-vis absorption spectra, we computed the energies of lower-lying excited states wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…All atoms were augmented with a single set of polarisation functions. Several publications have shown that the hybrid functional B3LYP is adequate for studying the electronic structures of π-conjugated systems such as those involving a phosphole moiety, [34] EDOT [35] or π-conjugated oligomers. [36] Second derivatives were calculated in order to check that the optimised structures are true minima on the potential energy surface.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…All atoms were augmented with a single set of polarisation functions. Several publications have shown that the hybrid functional B3LYP is adequate for studying the electronic structures of π-conjugated systems such as those involving a phosphole moiety, [34] EDOT [35] or π-conjugated oligomers. [36] Second derivatives were calculated in order to check that the optimised structures are true minima on the potential energy surface.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…[6] Theoretical studies on the phosphole-containing p-conjugated systems have promoted a better understanding of their structure-property relationships. [7] In addition to the above 2,5-disubstituted systems, ringfused p-systems, such as dibenzoA C H T U N G T R E N N U N G [b,d]phospholes and dithienoA C H T U N G T R E N N U N G [b,d]phospholes, have been receiving growing interest, as they possess rigid and elongated p-networks that are prerequisite for exhibiting high light-emitting ability. [8,9] In particular, Baumgartners dithienoA C H T U N G T R E N N U N G [b,d]phospholes have proven to emit intense fluorescence covering the blueyellow region.…”
Section: Introductionmentioning
confidence: 99%
“…The energy of these absorptions, attributed to p-p* transitions [8], depends dramatically on the nature of the 2,5-substituants of the phosphole ring (Table 1) [6,7]. The values of k max and the optical end absorption k onset (the solution optical 'HOMO-LUMO' gap) [1e], become red-shifted on replacing the 2-pyridyl groups (k max = 390 nm) by 2-thienyl rings (k max = 412 nm).…”
Section: Physical Propertiesmentioning
confidence: 99%